LAMENTING THE DISAPPEARANCE OF PRAGMATISM: SUBSIDIES LAW AFTER THE URUGUAY ROUND - Friedlander, Lara (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 1994)
Acceptance of the Uruguay Round Agreements marks a significant reorientation of the GATT from pragmatism to legalism. Not least among the measures affected by this shift is subsidies, an increasingly controversial area of trade law. Unlike the previous Track 1/ Track 2 method, GATT-legality of subsidies will be now be determined primarily by specificity and injury tests. This paper argues that the Uruguay Round Agreement on subsidies will eventually undermine the GATT as domestic pressures force states to ignore GATT rules. The paper goes on to suggest that subsidies law reform should concentrate on encouraging the use of the nonviolation nullification and impairment provision. As nonviolation nullification and impairment facilitates reciprocity by regulating reliance-induced behaviour, its legitimacy is stronger than that of the Uruguay Round Agreements. Such legitimacy is crucial when the viability of an international legal order depends on self-enforcement.